META-THEMATIC VECTOR OF PROSPECTIVE DEVELOPMENT OF MODERN HIGHER EDUCATION: competencies; development; future specialist; higher school; phenomenon - Dudka, Tetiana; Grebenyuk, Vyacheslav (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article outlines the problem of perspective development of modern higher schools applying the meta-thematic approach. The priority of the views of stakeholders and employers on the issue of improving the process of professional training, which correlates with modern demands of the current labor market. The purpose of the study is to theoretically outline the prospects of involving a meta-thematic approach to improving the process of training in a modern higher school. The purpose is produced by the need to conduct a comprehensive theoretical analysis of the stated issues from a psychological and pedagogical perspective, which reflects the level of correlation between the subject of the research and the peculiarities of personal development of all participants in the educational process. The multifaceted nature of the fundamental principles underlying the phenomenological crystallization produced by the influence of external, as well as internal determinants is detailed. The variability and multifunctionality of the researched subject, reflected at the level of organization and realization of the educational process following the full-fledged rationalization of educational and upbringing tasks are generalized. The research procedure involved the use of comparative, bibliographic, and problem methods to identify the basic essential characteristics of the studied phenomenon. At the level of such methodological system, the direct relation of the title phenomenon to the thought activity didactics, represented at the semantic level by the set of basic features (in particular, the priority of the activity component, didactic constructs, and reflexivity) is emphasized. Attention is drawn to the three-fold dimension of phenomenological extrapolation to the applied tasks of the modern educational process (meta-thematic activity, highly structured content framework, and extrapolation of the algorithmic system of knowledge to the real field of knowledge). The result of the research was the construction of a hierarchical structure of competency groups – effectiveness indicators of the educational process at the institution of higher education with a detailed description of their direct involvement in key levels of education and specific psychological components. The conclusions present the highly integrative nature of the subject in terms of its potential focus on solving a range of applied tasks. The phenomenological significance at the level of activation of the research, informational, organizational-managerial, and communicative component of prospective self-development and personal self-organization of all participants of the educational process is summarized